Large-Scale Dendrimer-Based Uneven Nanopatterns for the Study of Local RGD Density Effects on Cell Adhesion - Lagunas, Anna; Castaño, Albert G; Artés, Juan M; Vida-Pol, Yolanda; Collado-Martín, Daniel; Pérez-Inestrosa, Ezequiel; Gorostiza, Pau; Claros-Gil, Silvia; Andrades-Gómez, José Antonio; Samitier, Josep (My University, 2014)
Cell adhesion processes are governed by the nanoscale arrangement of the extracellular matrix (ECM), being more affected by local rather than global concentrations of cell adhesive ligands. In many cell-based studies, grafting of dendrimers on surfaces has shown the benefits of the local increase in concentration provided by the dendritic configuration, although the lack of any reported surface characterization has limited any direct correlation between dendrimer disposition and cell response. In order to establish a proper correlation, some control over dendrimer surface deposition is desirable. Here, dendrimer nanopatterning has been employed to address arginine–glycine–aspartic acid (RGD) density effects on cell adhesion. Nanopatterned surfaces were fully characterized by atomic force microscopy (AFM), scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS), showing that tunable distributions of cell adhesive ligands on the surface are obtained as a function of the initial dendrimer bulk concentration. Cell experiments showed a clear correlation with dendrimer surface layout: Substrates presenting regions of high local ligand density resulted in a higher percentage of adhered cells and a higher degree of maturation of focal adhesions (FAs). Therefore, dendrimer nanopatterning is presented as a suitable and controlled approach to address the effect of local ligand density on cell response. Moreover, due to the easy modification of dendrimer peripheral groups, dendrimer nanopatterning can be further extended to other ECM ligands having density effects on cells.
Keywords: Dendrímeros; Dendrimer; Arginine-glycine-aspartic acid; Atomic force microscopy; Scanning tunneling microscopy; Cell adhesion; Focal adhesions